Journal of Midwifery and Women's Health Vol.57, No.5, September/October 2012 - Wiley Subscription Services (Wiley-Blackwell, 2012)
-Advancing Midwifery: The American College of Nurse-Midwives' Documents and Publications -Recent Trends in Clinicians Providing Care to Pregnant Women in the United States -Comparasion of Perception of Pregnancy Risk of Nulliparous Women of Advanced Maternal Age and Younger Age -"The Midwifery Two-Step": A Study on Evidance Based Midwifery Practice -Differences in Quality of Antenatal Care Provided by Midwives to Low-Risk Pregnant Ducth Women in Defferent Ethic Groups -Diversity in the Scope and Practice of Hospital-Based Midwives in the Netherland -Birth Outcomes Assiciated with Receipt of Group Prenatal Care Among Low-Income Hispanic Women -Induced Abortion in Iran: Prevalence, Reasons, and Consequences